Manajemen Informasi Pada Organisasi: Studi Litratur Permasalahan Manajemen Pada Teknologi Informasi - Rizka Andini Nur Sabella rizka (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2021)
Literature review is a process of finding out and studying research results that have been published by researchers related to previous scientific work. Literature review activities can provide benefits for increasing knowledge related to the research being carried out. Relevant research and the results of previous research are really needed in making a good and correct literature review. The results of previous research and relevant research are useful for strengthening theories, ideas and phenomena that are related and influential in the formation of variables. In this article, the results of a review of factors that can influence performance in a company are presented. These factors include information technology, web-based information systems, knowledge about management, as well as literature reviews regarding Executive Support Systems (ESS) for Business. Results that can be obtained from literature review activities include, (1) The influence of information technology on employee performance; (2) Web-Based Information System on employee performance; (3) Knowledge Management